Konstruksi Perempuan Dalam Iklan Axe Battle: Perempuan Sebagai Mediatisasi Axe Battle 2014 - Intihaul Khiyaroh (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
This paper sees women as mediating between advertisements, websites and competitions. In this competition Chocolate type men fight Gold type men to be able to face beautiful and charming girls, Olivia Jensen. This competition was held in 2014 where there was an official website as a media that netted participants to the final event for the grand prize, namely women.